Biodegradable polymer drug-eluting stents versus first-generation durable polymer drug-eluting stents: A systematic review and meta-analysis of 12 randomized controlled trials - Bundhun, Pravesh Kumar (Medicine (Baltimore), 2017)
BACKGROUND: Even if drug-eluting stents (DES) showed beneficial effects in patients with coronary artery diseases (CADs), limitations have been observed with the first-generation durable polymer DES (DP-DES). Recently, biodegradable polymer DES (BP-DES) have been approved to be used as an alternative to DP-DES, with potential benefits. We aimed to systematically compare BP-DES with the first-generation DP-DES using a large number of randomized patients. METHODS: Electronic databases were searched for randomized controlled trials (RCTs) comparing BP-DES with first-generation DP-DES. The main endpoints were the long-term (≥2 years) adverse clinical outcomes that were reported with these 2 types of DES. We calculated odds ratios (ORs) with 95% confidence intervals (CIs) and the analysis was carried out by RevMan 5.3 software. RESULTS: Twelve trials with a total number of 13,480 patients (7730 and 5750 patients were treated by BP-DES and first-generation DP-DES, respectively) were included. During a long-term follow-up period of ≥2 years, mortality, myocardial infarction (MI), target lesion revascularization (TLR), and major adverse cardiac events (MACEs) were not significantly different between these 2 groups with OR: 0.84, 95% CI: 0.66–1.07; P = .16, I(2) = 0%, OR: 1.01, 95% CI: 0.45–2.27; P = .98, I(2) = 0%, OR: 0.91, 95% CI: 0.75–1.11; P = .37, I(2) = 0% and OR: 0.86, 95% CI: 0.44–1.67; P = .65, I(2) = 0%, respectively. Long-term total stent thrombosis (ST), definite ST, and probable ST were also not significantly different between BP-DES and the first-generation DP-DES with OR: 0.77, 95% CI: 0.50–1.18; P = .22, I(2) = 0%, OR: 0.71, 95% CI: 0.43–1.18; P = .19, I(2) = 0% and OR: 1.31, 95% CI: 0.56–3.08; P = .53, I(2) = 6%, respectively. CONCLUSION: Long-term mortality, MI, TLR, MACEs, and ST were not significantly different between BP-DES and the first-generation DP-DES. However, the follow-up period was restricted to only 3 years in this analysis.